COMPREHENSIVE ANALYSIS OF CHRONIC DISEASE MANAGEMENT STRATEGIES IN EVALUATING THE ROLE OF CLINICAL DIETITIANS AND NURSES IN PREVENTION, TREATMENT, AND PATIENT EDUCATION - Doaa Ali Yahya Madkali, Eman Ali Mohammed Sumayli, Shatha Hassan Ali Dahish, Abdulsalam Ali Madkhali, Abdulaziz Ali Mohammed Masmali, Rehab Mohammed Awaji Mahjari, Khulood Sohil Yahya Madkhali, Fatimah Mohammed Ali Kaby (Chelonian Research Foundation, 2022)
Chronic diseases are a very dramatic health problem for the public and need integrated solutions like prevention, treatment, and mitigation of their influence on the lives of people and society. Dietitians and nurses at the hospital, in particular, are the bedrock of the chronic disease management strategy. They have a wealth of skills, such as nutritional counseling, lifestyle modification, medication management, and patient education. This paper discusses effective chronic disease management strategies and also points out the contribution of special types of nurses and dietitians in the prevention, treatment, and education of patients. An assessment of relevant literature, methods used, and results achieved will be the focus of the following analysis, as it will be aimed at pointing out the approaches that work, the challenges that we face, and the recommendations on how to improve the chronic disease management role of clinical dietitians and nurses(Wang et.,al 2021). Keywords: chronic diseases' management, nutrition experts from the health centers, nurses, prevention and illness treatment, patient training.